Strategic process and organizational knowledge: Towards a pattern of strategic knowledge management - Damião Eneias de Melo dos Santos; Adriana Roseli Wünsch Takahashi (Tourism & Management Studies)
Knowledge Management has played an important role for organizational strategic processes. Thus, this work sought to examine the relation between strategic process and KM in the organization of an alimentary sector located in Brazil, namely, the company Frimesa. Through semi-structured interviews and non-participant observation, the proposed problem was instrumentalized. For that, the strategic process steps of this organization’s dairy line were identified from certain events; the knowledge flow and its application in the identified steps of the strategic process were investigated; and, finally, it was verified whether this relation configured a KM sample by means of promotion and knowledge sharing practices. The results of the pattern proposed point to the existence of a relation between strategic process and knowledge flow, with KM figuring as support for this relation, suggesting the existence of a strategic knowledge management.